The European Union as a Driver of Regional Cooperation in its Southern Neighbourhood - Gabriela Irina Ion (CES Working Papers, 2015)
The European Union's policy towards its southern periphery in North Africa and the Middle East has sought to promote regional cooperation both between itself and the Arab partner states and, most importantly, among the Arab states. The Euro-Mediterranean Partnership, and later on, the Union for the Mediterranean introduced, after decades of superficial institutionalization of Euro-Mediterranean relations, an element of novelty in the form of the regionalism it promoted and the multilateral setting it was creating. However outstanding at its debut, this experiment of ,,building” a Mediterranean region, where security and peaceful change would be brought about by the states' willingness to cooperate through multilateral mechanisms has failed. The EU's efforts to create a Mediterranean region have been stymied not only by what can amount to an unrealistic perception regarding intra-Arab dynamics, but also by changes in the substance of the Euro-Mediterranean institutional setting. Namely, the region-building multilateralism of the EMP has been side-lined by the pragmatic bilateralism of the UfM.
Keywords: F50; F53; F54; 330; bilateralism; Euro-Mediterranean Partnership; European Neighbourhood Policy; multilateralism; regionalism; region-building; Union for the Mediterranean